2018
DOI: 10.1038/s41574-018-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clocks and insulin resistance

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
333
0
26

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 480 publications
(404 citation statements)
references
References 244 publications
5
333
0
26
Order By: Relevance
“…Herein we discuss research findings relating to the proposed Circadian Syndrome risk components and comorbidities (Table 2). Hypertension Lack of nocturnal decline in blood pressure [30,62] High blood pressure [22] Lipids Disrupted lipid homeostasis [69,70] Obesity Disrupted diurnal rhythms in the white adipose tissue transcriptome [73] Obesity [22] Blood glucose levels Disrupted daily rhythms in blood glucose levels and glucose intolerance [17,21,75] Disrupted daily rhythms in blood glucose levels and glucose intolerance [22] Fatty liver Disrupted triglyceride accumulation, inflammation, oxidative stress and mitochondrial dysfunction [29] Depression Circadian disruption increases the incidences of depression [86,87] Circadian disruption increases the incidences of depression [22,83,84,[105][106][107][108][109][110] Sleep disturbances Circadian disturbances result in sleep loss and mistimed sleep [56,97] Proposing a Circadian Syndrome: Cardiovascular-related components Circadian oscillations have been reported for both physiological CVD regulation including heart rate and blood pressure [57], for cardiac disorders including arrythmias [58,59], and there is circadian variation in frequency of onset of myocardial infarction and sudden cardiac death [19,60].…”
Section: Circadian Disruption and Associations With Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein we discuss research findings relating to the proposed Circadian Syndrome risk components and comorbidities (Table 2). Hypertension Lack of nocturnal decline in blood pressure [30,62] High blood pressure [22] Lipids Disrupted lipid homeostasis [69,70] Obesity Disrupted diurnal rhythms in the white adipose tissue transcriptome [73] Obesity [22] Blood glucose levels Disrupted daily rhythms in blood glucose levels and glucose intolerance [17,21,75] Disrupted daily rhythms in blood glucose levels and glucose intolerance [22] Fatty liver Disrupted triglyceride accumulation, inflammation, oxidative stress and mitochondrial dysfunction [29] Depression Circadian disruption increases the incidences of depression [86,87] Circadian disruption increases the incidences of depression [22,83,84,[105][106][107][108][109][110] Sleep disturbances Circadian disturbances result in sleep loss and mistimed sleep [56,97] Proposing a Circadian Syndrome: Cardiovascular-related components Circadian oscillations have been reported for both physiological CVD regulation including heart rate and blood pressure [57], for cardiac disorders including arrythmias [58,59], and there is circadian variation in frequency of onset of myocardial infarction and sudden cardiac death [19,60].…”
Section: Circadian Disruption and Associations With Risk Factorsmentioning
confidence: 99%
“…This includes changes in light exposure resulting from the extensive use of artificial light (‘light pollution’) , controlled ambient temperature and constant food availability , societal and workplace stresses, increasing shift work in the workplace and industry, jet travel with time zone changes and changes in nutrition. In the light of this, it has been suggested that the resulting circadian rhythm disturbances may be a major contributor to the contemporary global epidemics of T2DM, CVD and obesity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional level of circadian regulation is the temporal modulation of enzymatic activity. 48,49,[51][52][53]57,59,94 At the cellular level, the NAD+/ NADH ratio, that represents an important sensor of energy metabolism, regulates the activity of clock components and plays a substantiate role in the fine tuning of the cellular core clock machinery to metabolic state. 93 Peripheral clocks play a key role in regulating carbohydrate, protein and lipid homeostasis ( Figure 1B).…”
Section: Of Mammalian Physiology and Metabolismmentioning
confidence: 99%
“…48,49,[51][52][53]57,59,94 At the cellular level, the NAD+/ NADH ratio, that represents an important sensor of energy metabolism, regulates the activity of clock components and plays a substantiate role in the fine tuning of the cellular core clock machinery to metabolic state. 31,59,71,77,[107][108][109][110][111] The nuclear receptor REV-ERBα is a key regulator of lipid, carbohydrate and protein metabolism. 103 An additional metabolic sensor in the body is the oxygen level.…”
Section: Of Mammalian Physiology and Metabolismmentioning
confidence: 99%